COVID-19 Pandemic and Agroecosystem Resilience: Early Insights for Building Better Futures - Duguma, L.A.; Noordwijk, M. van; Minang, Peter A.; Muthee, K. (MDPI, 2021)
The way the COVID-19 pandemic disrupted human lives and livelihoods constituted a stress test for agroecosystems in developing countries, as part of rural–urban systems and the global economy. We applied two conceptual schemes to dissect the evidence in peer-reviewed literature so far, as a basis for better understanding and enabling ‘building back better’. Reported positive impacts of the lockdown ‘anthropause’ on environmental conditions were likely only short-term, while progress towards sustainable development goals was more consistently set back especially for social aspects such as livelihood, employment, and income. The loss of interconnectedness, driving loss of assets, followed a ‘collapse’ cascade that included urban-to-rural migration due to loss of urban jobs, and illegal exploitation of forests and wildlife. Agricultural activities geared to international trade were generally disrupted, while more local markets flourished. Improved understanding of these pathways is needed for synergy between the emerging adaptive, mitigative, transformative, and reimaginative responses. Dominant efficiency-seeking strategies that increase fragility will have to be re-evaluated to be better prepared for further pandemics, that current Human–Nature interactions are likely to trigger.